Preparative Methods for Nanoanalysis of Materials with Focused Ion Beam Instruments - Philipp M. Nellen; Victor Callegari; Urs Sennhauser (CHIMIA, 2006)
Over the past 15 years, with materials research moving into sub-micrometer-dimensions, focused ion beam instruments (FIB) have proven to be a versatile tool to prepare samples for nanoanalysis. Especially advanced dual-beam FIBs, i.e. FIBs with a combination of an ion and electron column, take advantage of their particular features for imaging and preparation. This article discusses the principle of ion beam sample interaction to demonstrate how samples are prepared and what kind of possible sample damage and artifacts may occur. Typical FIB instrumentation is also addressed. Finally progress in FIB preparative methods for nanoanalysis of materials and also the common pitfalls to be avoided are discussed.